Nitrification of the lowermost stratosphere during the exceptionally cold Arctic winter 2015–2016 - M. Braun (Atmospheric Chemistry and Physics, 2019)
The Arctic winter 2015–2016 was characterized by exceptionally low stratospheric temperatures, favouring the formation of polar stratospheric clouds (PSCs) from mid-December until the end of February down to low stratospheric altitudes. Observations by GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) on HALO (High Altitude and LOng range research aircraft) during the PGS (POLSTRACC–GW-LCYCLE II–SALSA) campaign from December 2015 to March 2016 allow the investigation of the influence of denitrification on the lowermost stratosphere (LMS) with a high spatial resolution. Two-dimensional vertical cross sections of nitric acid (HNO3) along the flight track and tracer–tracer correlations derived from the GLORIA observations document detailed pictures of wide-spread nitrification of the Arctic LMS during the course of an entire winter. GLORIA observations show large-scale structures and local fine structures with enhanced absolute HNO3 volume mixing ratios reaching up to 11 ppbv at altitudes of 13 km in January and nitrified filaments persisting until the middle of March. Narrow coherent structures tilted with altitude of enhanced HNO3, observed in mid-January, are interpreted as regions recently nitrified by sublimating HNO3-containing particles. Overall, extensive nitrification of the LMS between 5.0 and 7.0 ppbv at potential temperature levels between 350 and 380 K is estimated. The GLORIA observations are compared with CLaMS (Chemical Lagrangian Model of the Stratosphere) simulations. The fundamental structures observed by GLORIA are well reproduced, but differences in the fine structures are diagnosed. Further, CLaMS predominantly underestimates the spatial extent of HNO3 maxima derived from the GLORIA observations as well as the overall nitrification of the LMS. Sensitivity simulations with CLaMS including (i) enhanced sedimentation rates in case of ice supersaturation (to resemble ice nucleation on nitric acid trihydrate (NAT)), (ii) a global temperature offset, (iii) modified growth rates (to resemble aspherical particles with larger surfaces) and (iv) temperature fluctuations (to resemble the impact of small-scale mountain waves) slightly improved the agreement with the GLORIA observations of individual flights. However, no parameter could be isolated which resulted in a general improvement for all flights. Still, the sensitivity simulations suggest that details of particle microphysics play a significant role for simulated LMS nitrification in January, while air subsidence, transport and mixing become increasingly important for the simulated HNO3 distributions towards the end of the winter.